(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
Patients with life-threatening illness experience both physical pain and personal suffering, with physical pain being normally circumscribed within the body of the patients’ and personal suffering reverberating also on the network of their personal relationships. Both of them can cause loneliness, in particular the so-called existential loneliness. This contribution focuses on the conditions that make it possible to experience this kind of loneliness as well as the theoretical issues that it raises, and outlines an ethical perspective for the caring of these patients.